Norm Localization and Security Communities: Amitav Acharya’s Framework Applied To The Thailand-Cambodia Preah Vihear Border Dispute - Mohd Radzi, Shamsul Azri; Jaafar, Faridah (Department of International Relations, Hasanuddin University, 2026)
The paper draws on Amitav Acharya’s theoretical frameworks of norm localization and security communities to examine the Thailand-Cambodia conflict over the Preah Vihear Temple, one of the most enduring international relations cases in Southeast Asia. The research will fill an important gap in the scientific literature by discussing how the constructivist ideas of Acharya shed light on the process of regional norm adaptation, identity formation, and the complications that arise when the (ASEAN) is forced to deal with an intra-mural territorial conflict as a fledgling security community. The study was based on using a qualitative case study approach with a secondary source analysis of the International Court of Justice proceedings, diplomatic archives, scholarly literature, and media archives to prove that local actors in both Thailand and Cambodia actively localized international norms of sovereignty, territorial integrity, and peaceful dispute settlement in a manner that both facilitated and hindered resolving conflicts. As the results demonstrate, the Preah Vihear conflict revealed underlying tensions within the ASEAN normative structure, especially between the principle of non-interference and the organization’s goal of becoming a mature security community. The article also examines the significant roles of the ASEAN chairmanship of Malaysia under Prime Minister Anwar Ibrahim and of United States President Donald Trump in mediating the crisis in 2025, focusing on the Kuala Lumpur Peace Accord, its failure, and the future of peaceful relations. The article leads to the study of International Relations by showing how Acharya’s framework can provide analytical resources for understanding norm-conflict in the Global South, while also criticizing Eurocentric approaches to norm diffusion and elucidating the role of peripheral actors in the formation of regional order.